Assessment of the effectiveness of participatory geographic information system (PGIS) in community development planning case of Santa Josefa, Agusan del Sur - Clavio, Pamela Christine L.; Castro, Jun T. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
Participatory Geographic Information System (PGIS) is a participatory mapping methodology which underpins participatory rural appraisal tools to carry out community development planning. PGIS contributes a different perspective to he usual sectoral and action planning done in the National Community Driven development Program implemented by the DSWD. PGIS's intention is to guide the local community in examining the physical factors contributing to their socio-economic vulnerabilities and eventually incorporating spatial issues into their development agenda. The growing body of PGIS literature provides substantial proof of the tool's potentials to support the emerging approaches and mandates of the Philippine government ;i,e., bottom-up, spatial, and evidence-based planning. Following the empowerment and information system success models, this study conceptualizes an assessment design that explores PGIS's influence in community development planning in Santa Josefa, Agusan del Sur. The primary objectives of the assessment include; a)differentiation in respondents' spatial awareness, planning perceptions and practice before and after PGIS intervention; b) determination of PGIS influence in public planning and decision-making activities of the barangay; c)understanding the relationship between the respondents' characteristics and PGIS effectiveness; and d) recommending strategic measures to improve PGIS application in community development planning. The study carried out a survey from a sample of 150 trained PGIS participants, conducted group discussions with the 11 barangays, and performed informant interviews with select MLGU office heads. Although the research was confined by several methodological and longitudinal limitations, the findings of the case study illustrate how both PGIS characteristics and PGIS users' attributes add to and impede the tool's successful implementation in community planning. The research results demonstrate that PGIS approach, specifically the use of satellite imagery, encourages community visualization of poverty challenges and aids in discourses about spatial and ecological issues in the barangay. The findings also illustrate how PGIS increases the geospatial skills among the participants as opposed to the traditional paper-and pen- method. After attending workshops on PGIS, the participants expressed a positive viewpoint towards community use of technologies and community involvement in mapping training. However, the research results reveal a decrease in community engagement during the PGIS mapping activity. In fact, from the findings, it shows that PGIS influence is only achieved by community people who are males, with high education, and from high-income classes.In general, the study provides information that deepens the understanding of PGIS context and effect to planning. The conclusions also strengthen the argument that PGIS application would lead to better bottom-up, spatial, and evidence-based approach if merged with barangay development planning activities. Because of this, part of the recommendations is for the LGUs to nurture a more participatory and better governance system if they intend to catalyze community confidence in technological developments such as PGIS. Future research activities may focus on refining the research framework used in this study and find other operational measures which can be used to comprehensively assess the effectiveness of PGIS in community planning.
Thesis (M.A. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Geographic information systems -- Philippines -- Santa Josefa (Agusan del Sur).; Participatory rural appraisal -- Philippines -- Santa Josefa (Agusan del Sur).; Rural development projects -- Philippines -- Santa Josefa (Agusan del Sur) -- Evaluation